From Stability to Mobility: African Secondary School Aged Adolescents' Transition to Mainstream Schooling. Issue 1 (8th July 2014) - Gunasekera, Sashya; Houghton, Stephen; Glasgow, Kenneth; Boyle, Christopher
Abstract : Setting clear achievable goals that enhance reputational status has been shown to direct the energies of adolescents into socially conforming or non-conforming activities. It appears to be the case that following transition from Intensive English Centres (IECs) into mainstream schooling, students from African refugee backgrounds experience difficulties in attaining the goals they had initially set, and in light of this become non-conforming. This present study investigates the goal setting, reputational status, and behaviour of 60 students from African refugee backgrounds prior to and following their transition into mainstream schooling. Findings revealed that prior to mainstream schooling, while in an IEC, these adolescents set specific academic goals, were highly committed to attaining them, sought a socially conforming reputation, and did not involve themselves in non-conforming activities. Within 6 months of transitioning into mainstream classes, however, these same adolescents set social goals commensurate with a non-conforming reputation, attached great importance to these goals, and evidenced significant increases in their delinquent and aggressive behaviour and significant reductions in their connectedness to school and teachers. These findings have important implications for assisting adolescent students from refugee backgrounds to develop clear, self-set achievable goals, and in supporting them through the process of attaining them following transition to mainstream schooling.